Comparison of two sub-optimum MLSE receivers for band-limited nonlinear channel - Khoo, Sunny Cheng Kong. (2008)
In this dissertation, we compared the performance of two sub-optimum receiver structure [1,2] for QPSK signals over a digital satellite communications channel, with downlink filtering following a nonlinear satellite transponder. The first receiver, Adaptive Threshold Detection with Estimated Sequence (ATDES) receiver [2] is capable of correcting channel degradation resulting from InterSymbol Interference and variations in transponder operating point encountered in a satellite communication system. The second receiver structure developed in [1], based on Average Matched Filter receiver, has also shown to perform well over various transponder back-off points.